Peritoneal cancer treatment with CYP2B1 transfected, microencapsulated cells and ifosfamide - Samel, Stephan Tim; Keese, Michael; Lux, Andreas; Jesenofsky, Ralf; Proßt, Rüdiger Lothar; Saller, R.; Hafner, M.; Sturm, Jörg; Post, Stefan; Löhr, J.-Matthias (Cancer gene therapy, 2006)
The prognosis of peritoneal spread from gastrointestinal cancer and subsequent malignant ascites is poor, and current medical treatments available are mostly ineffective. Targeted chemotherapy with intraperitoneal prodrug activation may be a beneficial new approach. L293 cells were genetically modified to express the cytochrome P450 enzyme 2B1 under the control of a cytomegalovirus immediate early promoter. This CYP2B1 enzyme converts ifosfamide to its active cytotoxic compounds. The cells are encapsulated in a cellulose sulfate formulation (Capcell™). Adult Balb/c mice were inoculated intraperitoneally with 1 × 106 colon 26 cancer cells, previously transfected with GFP to emit a stable green fluorescence, by injection into the left lower abdominal quadrant. Two or five day's later animals were randomly subjected to either i.p. treatment with ifosfamide alone or ifosfamide combined with microencapsulated CYP2B1-expressing cells. Peritoneal tumor volume and tumor viability were assessed 10 days after tumor inoculation by means of fluorescence microscopy, spectroscopy and histology. Early i.p. treatment with ifosfamide and CYP2B1 cells resulted in a complete response. Treatment starting on day 5 and single-drug treatment with ifosfamide resulted in a partial response. These results suggest that targeted i.p. chemotherapy using a combination of a prodrug and its converting enzyme may be a successful treatment strategy for peritoneal spread from colorectal cancer.
Published: 12 August 2005
Gesehen am 23.05.2022